2022
DOI: 10.3390/app12031176
|View full text |Cite
|
Sign up to set email alerts
|

Influence of MnO2-Birnessite Microstructure on the Electrochemical Performance of Aqueous Zinc Ion Batteries

Abstract: KxMnO2 materials with birnessite-type structure are synthetized by two different methods which make it possible to obtain manganese oxides with different degrees of crystallinity. The XPS results indicate that the sample obtained at high temperature (KMn8) exhibits a lower oxidation state for manganese ions as well as a denser morphology. Both characteristics could explain the lower capacity value obtained for this electrode. In contrast, the sample obtained at low temperature (KMn4) or by hydrothermal method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…These experiments confirm the presence of K + and H 2 O species within the structure of both samples, as previously reported. 21 Indeed, the quantity of these interlayer species is a critical factor for the emergence of one phase or the other. 30 It can be observed that T-KMn (δ-MnO 2 lamellar phase) shows higher content of K + and H 2 O than SG-KMn (α-MnO2 tunnelled phase), in agreement with previously reported results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These experiments confirm the presence of K + and H 2 O species within the structure of both samples, as previously reported. 21 Indeed, the quantity of these interlayer species is a critical factor for the emergence of one phase or the other. 30 It can be observed that T-KMn (δ-MnO 2 lamellar phase) shows higher content of K + and H 2 O than SG-KMn (α-MnO2 tunnelled phase), in agreement with previously reported results.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, MnO 2 structures offer a wide variety of crystal structures and chemistries to be unravelled as promising efficient cathode materials for AIBs. 18 Within the vast manganese dioxide family, α-MnO 2 (cryptomelanelike) has been reported as an electrode in aqueous AIB, 19 aqueous zinc-ion, 20,21 and lithium batteries. 18,22 The extensive study of different hollandite-type electrode materials is largely due to the particular octahedra framework of this structure-type.…”
mentioning
confidence: 99%
“…Mn oxides are a popular choice as the ZIB cathode, with numerous studies exploring the performance of different MnO 2 polymorphs in this application. ,, Multiple reaction mechanisms have been reported in Zn–Mn batteries, including intercalation of Zn 2+ /H + into the MnO 2 lattice tunnels or layers, direct conversion of MnO 2 to MnOOH, and a dissolution-deposition reaction oscillating between MnO 2 (or another phase containing Mn 3+/4+ such as chalcophanite or vernadite) and Mn 2+ on charge and discharge, respectively. , These mechanisms are not necessarily exclusive of each other, as Huang et al reported a mixed insertion of Zn 2+ and H + that promoted a conversion reaction of MnO 2 into Zn x MnO 4 , MnOOH, and Mn 2 O 3 when using α-MnO 2 …”
mentioning
confidence: 99%